Identification of Novel Dermoscopic Patterns for “Featureless Melanoma”: Clinical-Pathological Correlation - Lampitelli, Salvatore; Cantisani, Carmen; Rega, Federica; Chello, Camilla; Farnetani, Francesca; Pellacani, Giovanni (Dermatology Practical & Conceptual, 2023)
Introduction:Diagnosis of melanoma can be sometimes very difficult because of its phenotypic and histological heterogeneity.Difficult-to-diagnose melanoma can be represented by mucosal melanoma, pink lesions, amelanotic melanoma (amelanotic lentigo maligna, amelanotic acral melanoma, desmoplastic melanoma), melanoma arising on sun-damaged facial skin, and “featureless melanoma”.Objective:The aim of the study was to improve the identification of featureless melanoma (scoring 0-2 according to 7-point-checklist)describing the variegated dermoscopical features and their histo-pathological correlation.Methods:Study samples included all melanomas excised based on clinical and/or dermoscopic findings in the period between January 2017 and April 2021.Before excisional biopsy, all lesions were recorded by means of digital dermoscopy at the department of Dermatology.Only lesions with a diagnosis of melanoma and a high quality of dermoscopic images were included in this study. After clinical and dermoscopic evaluation of 7-point checklist score, single dermoscopic and histological features were considered for lesions with a score of 2 or lower and a diagnosis of melanoma (corresponding to dermoscopic featureless melanoma).Results:A total of 691 melanomas fulfilled inclusion criteria and were retrieved from the database. The 7-point checklist evaluation identified 19 “negative-featureless” melanoma.The 100% of the lesions with score 1 showed a globular pattern. Conlusions:Dermoscopy is still the best diagnostic method for melanoma. The 7-point checklist provides a simplification of standard pattern analysis because of the algorithm based on a scoring system and the lower number of features to recognize. In the daily practice it is more comfortable for many clinicians to keep in mind a list of principles that may help in the decision.